An investigation on wind/PV/fuel cell/battery hybrid renewable energy system for nursing home in Istanbul - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2019)
This paper presents a techno-economic analysis of hybrid renewable energy systems to supply the electrical load requirements of the nursing home located in Istanbul, Turkey. The standalone hybrid renewable energy systems (Photovoltaic (PV)/wind/fuel cell/electrolyzer, PV/fuel cell/electrolyzer, and wind/fuel cell/electrolyzer, etc.) considered in the analysis were comprised of different combinations of PV panels, fuel cells, and wind turbines supplemented with hydrogen storage. In this study, the Hybrid Optimization of Multiple Energy Resources (HOMER) software is used as the assessment tool to determine the optimal configuration of hybrid renewable energy systems taking total net present cost and cost of energy into consideration. As a result, it is determined that the optimal system configuration of standalone wind/PV/fuel cell/electrolyzer hybrid renewable energy systems with the lowest total net present cost consists of 30 kW PV panel, 20 kW wind turbine, 20 kW fuel cell, 20 kW power converter, 50 kW electrolyzer, 20 kW rectifier, and 100 kg hydrogen tank. Besides, the net present cost and cost of energy of the optimum configuration are calculated to be $607,298 and $1.306/kWh, respectively. The system is considered as completely renewable. When wind speed and solar radiation values increase, then the cost of energy decrease about $0.979/kWh.
Keywords: Hydrogen storage systems; solar panels; wind turbines; hybrid renewable energy systems; WIND ENERGY; POWER; HYDROGEN